2020
DOI: 10.1101/2020.10.07.20208603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serological Analysis Reveals an Imbalanced IgG Subclass Composition Associated with COVID-19 Disease Severity

Abstract: COVID-19 is associated with a wide spectrum of disease severity, ranging from asymptomatic to acute respiratory distress syndrome (ARDS). Paradoxically, a direct relationship has been suggested between COVID-19 disease severity, and the levels of circulating SARS-CoV-2-specific antibodies, including virus neutralizing titers. Through a serological analysis of serum samples from 536 convalescent healthcare workers, we found that SARS-CoV-2-specific and virus-neutralizing antibody levels were indeed elevated in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 31 publications
3
28
2
Order By: Relevance
“…We also quantitatively examined the IgG1 and IgG3 subclass response and found that in our study population IgG1 appeared to be by far the dominant IgG subtype. This is in contrast to previous studies that suggest an IgG subclass ratio skewed towards IgG3 during SARS-CoV-2 infection [33,39]. A possible explanation for this discrepancy is that in these studies the plasma samples were collected shortly after COVID-19 disease recovery, while in our study samples were collected up to 22 weeks after onset of All rights reserved.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…We also quantitatively examined the IgG1 and IgG3 subclass response and found that in our study population IgG1 appeared to be by far the dominant IgG subtype. This is in contrast to previous studies that suggest an IgG subclass ratio skewed towards IgG3 during SARS-CoV-2 infection [33,39]. A possible explanation for this discrepancy is that in these studies the plasma samples were collected shortly after COVID-19 disease recovery, while in our study samples were collected up to 22 weeks after onset of All rights reserved.…”
Section: Discussioncontrasting
confidence: 85%
“…We observed that IgG anti-RBD consisted mainly of IgG1, median for IgG3 is 2.5% (IQR 1.5 – 5.1%; Figure S2A). Since higher subclass ratios were reported for antibodies against the S2 vs S1 domain of the S protein [32, 33], we also tested IgG1 and IgG3 in a subset of samples against the full S protein, but we obtained very similar results (Figure S2B).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…More importantly, Yates et. al demonstrated spike-specific IgG1, and not IgG3 was closely correlated with in vitro viral neutralization, and greater proportion of S1 or RBD-specific IgG3 was associated with COVID-19 disease severity (32). The dynamics of IgG1 and IgG3 was similar to IgG when duration or severity was considered, with IgG1 showing no difference in the third week.…”
Section: Discussionmentioning
confidence: 95%
“…Alveolar capillary microthrombi are nine times more prevalent in COVID-19 than in influenza autopsies (Lax et al, 2020). Patients exhibit elevated D-dimer levels and widespread thrombotic microvascular injury (De Voeght et al, 2020;Rapkiewicz et al, 2020). Several studies suggest altered platelet immune cell interactions (Leppkes et al, 2020, Manne et al, 2020 and the presence of megakaryocytes (MKs) in affected lungs (Meyerholz and McCray, 2020).…”
Section: Introductionmentioning
confidence: 99%